Measurement of Glomerular Filtration Rate (GFR) in an Ectopic Pelvic Kidney by Dual Head Gamma Camera (Bangladesh Journal of Nuclear Medicine, 2018)
Background: DTPA renogram is an accepted method to measure glomerular filtration rate (GFR) of the kidneys. The function of an ectopic kidney varies on the basis of its size, shape, position and rotation. This may lead to variation in tissue attenuation and error in computed GFR and differential renal function (DRF) of each kidney. The objectives of this study was to assess  the changes in the GFR measurement of an ectopic kidney in a dual head gamma camera using anterior and posterior imaging process and its influence on quantification of total GFR.Patients and Method: A Total 20 patients having one ectopic pelvic kidney and other normal positioning kidney were enrolled in the study. DTPA renogram images were acquired on a dual head gamma camera (Symbia T2) in anterior and posterior views simultaneously. Both anterior and posterior images data were used separately to compute the GFR. Three sets of total GFR of both kidneys were calculated separately. In set I, total GFR (ant) is equal to sum of both kidneys GFR in anterior imaging process, in set II total GFR (post) is equal to sum of both kidneys GFR in posterior imaging process and in set III total GFR (ectopic .ant + normal. post) is equal to sum of the GFR of normal kidney on posterior image and the GFR of ectopic kidney on anterior image. These three sets of total GFRs were compared with the patient’s eGFR measured by Cockcroft Gault formula.Result: Mean age of the patient was 36.9 ± 14.6 years (range 18-70 years). Mean total GFR (ant)   was 89.2±11.6 ml/min, total GFR (post) was 82.9±13.4 ml/min and total GFR (ectopic .ant + normal.post) was 102.5±15.9 ml/min. Mean eGFR is 101.93±24.9ml/min. When these three sets of DTPA assisted GFR compare with eGFR the Pearson’s correlation coefficient r= 0.45, 0.55 (P